Analysis of Onion Marketing Structure in Yola North Local Government Area of Adamawa State, Nigeria - Ahmed, Muhammad Auwal; Idris, Abdulazeez; Chinda, Maurice David (International Journal of Scientific Research and Management (IJSRM), 2018)
This study analyzed the structure of onion marketing in Yola North Local Government Area of Adamawa State, Nigeria. Data were collected from Jimeta Modern market, Old market and Yola by-pass market based on the existing sampling frame. Descriptive statistics, Gini index and Marketing efficiency were the analytical tools employed. The results revealed that majority (92.5%) of the respondents were male, 62.5% were married with an average family size of 4 persons per household and 52.5% had some level of formal education with a mean marketing experience of 10 years. The average sales recorded per month for wholesalers and retailers were N2,888,000.00 and N372,237.50 respectively, while their respective net incomes per month were N234,610.00 and N35,743.73 respectively. The value of Gini coefficient for wholesalers and retailers were 0.47 and 0.52 respectively, an indication of inequality in earnings among the marketers due to high market concentration resulting to poor market structure. The results further revealed that onion marketing is inefficient in the study area with marketing efficiency scores of 8.82% and 10.62% for wholesalers and retailers respectively. The Return on Investment (ROI) for wholesalers and retailers were N0.081 and N0.096 respectively with retailers having relatively higher ROI. Lack of credit facilities (80%), high cost of transportation (73%) and security challenges (42.5%) were identified as the major problems affecting onion marketers in the area. The study recommends that government should expand its anchor borrower scheme program to include marketers in order to enable them expand their business and improve marketing efficiency.